engaruh Store Atmosphere dan Word Of Mouth terhadap Keputusan Pembelian (Survei Pada Pelanggan Restoran Bebek Tepi Empang Kecamatan Tambun Selatan Kabupaten Bekasi) - Isarma Adiningtias; Dadan Ahmad Fadili (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
Abstract: The increasing activity of people who are increasingly busy in urban areas is one of the factors of business opportunities in the culinary field, causing many restaurants to appear as they are today. This research aims to determine, analyze and explain whether Store Atmosphere and Word of Mouth have a partial or simultaneous influence on purchasing decisions at Bebek Tepi Empang Restaurant. This research uses descriptive analysis and verification quantitative methods. The sample in this research used a non-probability sampling technique with an incidental sample method of 150 people using a Likert scale technique and path analysis. The correlation coefficient between Store Atmosphere and Word of Mouth obtained a value of 0.668, which means that the correlation is strong, positive and significant. The partial effect of Store Atmosphere on purchasing decisions has a greater value of 40.9% while Word of Mouth on purchasing decisions has a value of 18.7%. Simultaneous effect of Store Atmosphere, Word of Mouth on purchasing decisions has a value of 59.7%, the remaining 40.3% is influenced by other variables not examined.